2014
DOI: 10.1016/j.infbeh.2014.08.001
|View full text |Cite
|
Sign up to set email alerts
|

Preterm infants’ orally directed behaviors and behavioral state responses to the integrated H-HOPE intervention

Abstract: Preterm infants are challenged by immature infant behavioral organization which may negatively influence their ability to oral feed. The purpose of this study was to determine whether the integrated H-HOPE (Hospital to Home: Optimizing the Infant’s Environment) intervention would improve infant behavioral organization by increasing the frequency of orally directed behaviors and the proportion of time spent in an alert behavioral state when offered prior to oral feeding. Mother–infant dyads (n = 198) were rando… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 61 publications
(98 reference statements)
0
23
0
Order By: Relevance
“…18,85120 Eight articles were on the Auditory, Tactile, Vestibular, Visual (ATVV) intervention originally described by Rosemary White-Traut, two on the Family Nurture intervention, 99,113 three on the Hospital to Home: Optimizing the Premature Infant's Environment (H-HOPE) intervention, 114,115,120 one on massage with aromatic oil, 112 three on use of kangaroo care coupled with auditory stimuli 87,108,111 and 20 described a massage intervention that was coupled with a kinesthetic component. 85,86,8998,100,102107,109 …”
Section: Resultsmentioning
confidence: 99%
“…18,85120 Eight articles were on the Auditory, Tactile, Vestibular, Visual (ATVV) intervention originally described by Rosemary White-Traut, two on the Family Nurture intervention, 99,113 three on the Hospital to Home: Optimizing the Premature Infant's Environment (H-HOPE) intervention, 114,115,120 one on massage with aromatic oil, 112 three on use of kangaroo care coupled with auditory stimuli 87,108,111 and 20 described a massage intervention that was coupled with a kinesthetic component. 85,86,8998,100,102107,109 …”
Section: Resultsmentioning
confidence: 99%
“…The interventions include but are not limited to oral sensory stimulation, 52 non-nutritive sucking, 38,5355 and multisensory intervention. 42,43,56 While these interventions have been shown to improve alert states, little research has identified sleep states or crying in response to these interventions. The findings from this research confirm the influence of behavioral states immediately prior to feeding on oral feeding efficiency, and thus may be instrumental in future designing and testing of interventions that facilitate optimal behavioral states for oral feeding in preterm infants.…”
Section: Discussionmentioning
confidence: 99%
“…self-identified as Black or Latina, less than high school education, less than 18 years old, history of current mental illness, family income less than 150% of poverty, more than one child under 24 months, four or more children under four in the household, or residing in a disadvantage neighborhood. 41,42 Infants were excluded if they had congenital anomalies, necrotizing enterocolitis, positive finding on head ultrasound (e.g. cystic PVL or grade III or IV IVH), receiving assisted ventilation at the time of enrollment, chronic lung disease, and/or prenatal drug exposure.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…They include mouthing, tonguing, rooting, hand-to-mouth, and sucking-on-hand [6, 17, 26, 28]. In full term infants, orally-directed behaviors emerge in the first hour following birth.…”
Section: Introductionmentioning
confidence: 99%